Fiber optic turbidity sensor for water quality monitoring - Soh, Dominic Wei Xiang. (2010)
Current and conventional methods for measuring turbidity has certain limitations, ranging from being inaccurate (for the case of the Secchi disk and the turbidity tube) and being easily damaged (for turbidimeters). Being chemically passive, non-electrical, immune to electromagnetic interference and able to perform in harsh environments, fiber optic turbidity sensors can be fabricated and developed for the use of onsite, in situ and remote turbidity measurements of stagnant water bodies as well as moving water channels.